Investigation of mechanical properties based on the particle size of alumina ceramics prepared by circulatory bead milling. Issue 19 (1st October 2022) - Dixit, Prashant; Rawal, Bhupender; Panda, Himanshu Sekhar; Kumar, B. Praveen
Abstract: The combined action of circulatory grinding and bead milling on the microstructure and mechanical characteristics of alumina was examined in this study. Reduction in particle size of as received alumina powder was obtained under different milling durations: 0, 6, 15 and 20 h (hereafter abbreviated as BM00, BM06, BM15 and BM20, respectively). X-ray diffraction studies revealed the conspicuous effect of milling duration on FWHM, crystalline size and crystallinity. The alumina powder's field emission scanning electron micrograph displayed the finest particles (D50 -170 nm) in BM15 samples, which achieved a uniform grain size (∼1 μm) and relative density of ∼96% after sintering at 1600 ° C. Ultrasonic interferometer study has also been utilized because wave velocity depends on the elastic properties of the propagation medium, and using this phenomenon, compressibility (β), Young's modulus (E) and ballistic energy dissipation ability (D-criterion) of the prepared ceramics have been calculated. The bead milled samples exhibited substantial improvement in mechanical properties as compared to as-received powder, and BM15 samples achieved the highest hardness (17 GPa), flexural strength (389 MPa), fracture toughness (4.13 MPa m 1/2 ) and compressive strength (2290 MPa) values.